2005
DOI: 10.1111/j.1464-410x.2005.05422.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of vasoactive intestinal polypeptide into the penis improves erectile response in the diabetic rat

Abstract: 1.5 ms, 20 V, 1 min) were measured in subsamples of rats at 1, 3, 7 and 14 days after injection; after measuring the ICP the animals were killed, and penile, hepatic, renal artery and abdominal aorta tissue samples were frozen in liquid nitrogen and stored at -80 ∞ C. The gene expression of VIP in all samples, assessed as the expression of VIP mRNA, was estimated using a semiquantitative reverse-transcription polymerase chain reaction. RESULTSThe mean amplitude of ICP and expression of VIP mRNA in the cavernos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Several genes have been targeted for possible therapies, including hSlo calcium-sensitive K þ channel, endothelial nitric oxide synthase, (neuronal nitric oxide synthase , vascular endothelial growth factor (VEGF), vasoactive intestinal peptide and brain-derived neurotrophic factor. [2][3][4][5][6][7][8] Many techniques of gene delivery systems exist, each with their respective advantages and disadvantages. Viral delivery systems remain the most widely used in research today.…”
Section: Introductionmentioning
confidence: 99%
“…Several genes have been targeted for possible therapies, including hSlo calcium-sensitive K þ channel, endothelial nitric oxide synthase, (neuronal nitric oxide synthase , vascular endothelial growth factor (VEGF), vasoactive intestinal peptide and brain-derived neurotrophic factor. [2][3][4][5][6][7][8] Many techniques of gene delivery systems exist, each with their respective advantages and disadvantages. Viral delivery systems remain the most widely used in research today.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have used vectors to insert genes for vascular endothelial growth factor, nitric oxide synthase, preprocalcitonin gene-related peptide, and vasoactive intestinal peptide into the corporal bodies of rodents. [15][16][17][18][19][20][21] These studies all have demonstrated improved erections and cavernous pressures in response to stimuli in the rat. However, these strategies have relied on vectors inserting genes into the host chromosomes, and this introduces the potential for insertion into unintended targets.…”
Section: Gene Therapy For Edmentioning
confidence: 92%
“…Intracavernous injection of adenovirus vector prepro-CGRP into aged rats resulted in increased levels of CGRP protein and cAMP, as well as higher ICP on cavernosal nerve stimulation compared to untreated control patients 5 days after treatment [71]. Vasoactive intestinal peptide (VIP) is another modulator of smooth muscle tone, and transfection of penile corpora cavernosa with pcDNA3/VIP cDNA in STZ-diabetic rats resulted in higher ICP and sustained expression of VIP mRNA for 2 weeks or more in the penis in vivo [72].…”
Section: Modulator Of Ion Channels In Smooth Muscle Cellsmentioning
confidence: 95%